AKTIVITAS ANTIOKSIDAN PADA SERBUK INSTAN DARI CAMPURAN BUAH DAN SAYUR (MANGGA, SEMANGKA, MENTIMUN, WORTEL, BROKOLI) - Husnani, Husnani; Nadia (Akademi Farmasi Yarsi Pontianak, 2023)
Instant powder beverages are beverages made from either fresh or dried ingredients that are boiled for more or less than 60 minutes, then sugar or no sugar is added and the water is evaporated until sugar crystals or powder are obtained. Fruits and vegetables from mango, watermelon, cucumber, carrots and broccoli have many health benefits as natural antioxidants. This study aims to determine the instant powder with the highest antioxidant activity from a mixture of fruits and vegetables or a mixture of ginger, temulawak, turmeric and lemongrass. This study was conducted experimentally by examining each instant powder preparation from a mixture of fruits and vegetables on antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method and UV-Vis spectrophotometer. The results showed that the instant powder drink from a mixture of fruits and vegetables had antioxidant activity with an IC50 value of 100.341. These results indicate that instant powder from a mixture of fruits and vegetables has strong antioxidant potential.